Strengthening Students’ Academic Ethics Through a Digital Citizenship–Based Social Education Model - Wingkolatin, Wingkolatin; Aprijane A, Ketlin; Rintaningrum, Ratna; Pradana, Mahir; Nuswantara, Kartika; Dewi, Dinda Aura (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to analyze and formulate a digital citizenship–based social education model in the context of strengthening the academic ethics of students in the Pancasila and Civic Education Study Program, Faculty of Teacher Training and Education, Universitas Mulawarman. This research employed a qualitative approach with a case study design. Data were collected through observations of the learning process, in-depth interviews, and document analysis. The research informants consisted of ten students, six lecturers responsible for courses related to character education, social education, digital literacy, professional ethics, citizenship, and educational technology, as well as faculty and study program leaders. Data analysis was conducted systematically through the stages of data reduction, data display, and conclusion drawing. The findings indicate that digital citizenship is understood by informants as a value-based framework relevant to fostering ethical awareness, academic responsibility, and students’ digital citizenship attitudes in the use of technology and artificial intelligence. The formulated social education model emphasizes value-oriented learning objectives, contextual learning materials, reflective and participatory methods, ethical utilization of digital media, and evaluation oriented toward academic attitudes and behavior. These findings suggest that digital citizenship–based social education has a strategic role as a conceptual framework for strengthening students’ academic ethics in the era of artificial intelligence.